Analysis of factors influencing MOOC quality based on I-DEMATEL-ISM method - Liang Zhou; Mingyun Tang; Jian Liu (Systems and Soft Computing)
The quality of MOOCs is influenced by multiple factors. This paper proposes a new method, I-DEMATEL-ISM, which combines intuitionistic fuzzy sets with DEMATEL (Decision testing and evaluation laboratory) and ISM (Interpretive structural modeling), to analyze the relationships between these factors and identify strategies for improving MOOC quality. In the first, six key factors were selected through literature research and expert consultations. Then, the interrelationships between the six factors were analyzed. Finally, interpretive structural modeling was established. The analysis revealed that course teachers are fundamental factors, while course content and management are intermediate factors. Learning platforms, tasks, and materials are surface factors. Improving surface factors can enhance MOOC quality in the short term, while improving intermediate and fundamental factors can create a sustainable cycle of quality improvement.